U źródeł cyrylickiego piśmiennictwa południowosłowiańskiego oraz jego percepcji na gruncie wschodniosłowiańskim i polskim - Białokozowicz, Bazyli (Acta Polono-Ruthenica, 2006)
This article presents an introductory part of my lecture Russian culture and civilization in the Slavic and world context. An information about presumable themes for the XVI International congress of the Slavic scholars in Ohrid (Macedonia) in 2008 were approved by the Presidium of the International Committee of the Slavic scholars in Opole (Poland), September 2004). A considerable part of this article is assigned to the epoch of Cyril and Methodius, the emergence of two Slavonic alphabets (Cyrillic and Glagolitic), the development of Slavonic written language in Macedonia with due regard for Ohrid Slavic culture. The Prior of the Holy Altar, the Head of the Roman Catholic Church Pope John Paul II in the epistle Slavorum Apostoli 2 VI 1985 attached the utmost importance to their activity not only for Slavic world but also for the whole Europe and also underlined that the beginning of the Christianity in Poland came into contact with Cyril and Methodius tradition. A Christening of Russia (988) was conductive to this process „becoming the part of our state, public, cultural, church life”(Richard Luzny). Polish archival and book collections contain the huge number of Cyril and Methodius manuscripts and the first typescript editions what creates highly auspicious conditions for the research work in the different fields of Slavic study.